2018
DOI: 10.1111/1365-2745.13113
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of large herbivores in a reassembling African ecosystem

Abstract: 1. Megafauna assemblages have declined or disappeared throughout much of the world, and many efforts are underway to restore them. Understanding the trophic ecology of such reassembling systems is necessary for predicting recovery dynamics, guiding management, and testing general theory. Yet, there are few studies of recovering large-mammal communities, and fewer still that have characterized food-web structure with high taxonomic resolution.2. In Gorongosa National Park, large herbivores have rebounded from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 120 publications
3
93
0
Order By: Relevance
“…However, wild pig and muntjac were poorly sampled in this study and any definitive conclusion about their diet is not possible. Our data do support herbivore community studies that indicate feeding mode, and not body size or phylogeny determine niche breadth (Bagchi et al, ; Kartzinel et al, ; Lintulawkso & Kovarovic, ; Pansu et al, ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, wild pig and muntjac were poorly sampled in this study and any definitive conclusion about their diet is not possible. Our data do support herbivore community studies that indicate feeding mode, and not body size or phylogeny determine niche breadth (Bagchi et al, ; Kartzinel et al, ; Lintulawkso & Kovarovic, ; Pansu et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Multiple studies in African systems have demonstrated the complexity of foraging strategies among ungulate communities, with species arrayed along a continuum that reflects differences in body size (Cummings & Cummings, ; Fritz & Loison, ; Hopcraft et al, ), morphology (Pansu et al, ) phylogeny (Pérez‐Barbería, Gordon, & Nores, ), and behavior (Owen‐Smith, ). Kartzinel et al () found body size a coarse indicator of grass versus woody species consumption, but pairs of similar body‐size species differed in the specific plant species consumed.…”
Section: Discussionmentioning
confidence: 99%
“…To test the prediction that digestible energy and protein content would be significantly higher in cultivated crop plants than in natural‐forage species consumed by elephants within the Park (P3), we first quantified diet composition of elephants using DNA metabarcoding (Kartzinel et al., ; Pansu et al., ) of 21 fresh faecal samples collected inside GNP during the dry season (June–August) of 2016. We collected samples during immobilizations and also opportunistically after observing elephants defecating and then waiting for them to leave the area.…”
Section: Methodsmentioning
confidence: 99%
“…Sample collection and processing followed protocols described by Pansu et al. (), and a detailed description of the metabarcoding protocol and analyses is provided in Supporting information Appendix C.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the results obtained so far provide substantial knowledge toward effective conservation planning and management, by identifying the impacts of introduced species, both revealing competition with native fauna (Brown et al, ; Egeter, Bishop, & Robertson, ; Robeson II et al, ; Zarzoso‐Lacoste et al, ) and uncovering the importance of introduced plant species to the diet of endangered species (Ando et al, ). There have also been some studies focusing on the diets of reintroduced or recovering populations (Kowalczyk et al, ; Pansu et al, ; Pinho et al, ) and on the effects of hunting in niche partitioning between both herbivores (Pansu et al, ) and carnivores (Smith et al, ). Additionally, the effects of pollution have been addressed twice, with light pollution having species‐specific effects on bats' feeding habits (Cravens et al, ) and trace metal pollution modulating food preferences of the wood mouse Apodemus sylvaticus (Ozaki et al, ).…”
Section: Important New Research Avenues From Diet Studies Using Dna Mmentioning
confidence: 99%